Swap Between Short-Term Financing and Short-Term Investment to Increase Revenues Applied research in the soft drinks company - Lecturer Dr. Ibrahim S. Abdullah Alshammary (Scholars Digest Publishing, 2022)
This research comes in the context of dialectical knowledge of the relationship between short-term financing and short-term investment to increase revenues, which gives the company's management the freedom to make the appropriate financial decision in both sides of financing (short-term) and investment (short-term) and accordingly the search was on the financial statements related to the three research variables mentioned above in B Ghaddad Company for soft drinks and listed in the Iraq Stock Exchange And for (20) years extended from (20 22-20 03) based on a number of statistical research methods.
Keywords: Short-term financing, short-term investment, Revenue, Soft Drinks Company